KONFIGURASI POLITIK SEBAGAI BAGIAN DARI PEMBENTUKAN DAN PERKEMBANGAN HUKUM - Agus, Agus; Iswandi, Iswandi; Mardhatillah, Mardhatillah (Ensiklopedia of Journal, 2024)
Abstract: Political configuration greatly influences the creation and development of law, Its proven by the law statement  is a political product. The purpose of this study is to analyze the dominant  legal political  configuration that influences the formation and development of law in the world, especially in Indonesian conducting  analysis of the configuration of legal politics, a literature study was carried out using the legal history approach and the statutory regulating approach. The results of this study intent that the configuration of legal politics in Indonesia. This study  is very much influenced by the civil law system while still considering other legal principles (common law which in Indonesia is known as customary law). The formation of law in Indonesia is a consequence of the adoption of the civil law system, but it does not mean that its formation and pay attention to aspects that exist in society. it can be seen in the provisions of Law Number  12 of 2011 concerning the Formation of Legislation which regulated that in order for the regulations made become quality, they must pay attention to and struct 3 (three) foundations, namely: 1) Philosophical Foundation (filosofische grondslag), that is  considerations  illustrate  the regulations formed take into account the outlook on life, awareness and legal ideals which include the spiritual atmosphere and philosophy of the Indonesian nation which are sourced from Pancasila and the Preamble to the 1945 Constitution, 2) Sociological Foundation (sosiologische grondslag), namely considerations that describe regulations formed to meet the needs of society in various aspects, and 3) Juridical Foundation (juridische grondslag), namely considerations  illustrate  regulations formed to fill legal gaps by taking into account existing regulations, it will be changed or revoked in order to guarantee legal certainty and a sense of justice in society.Keywords: Configuration, Political, Law.